2001
DOI: 10.1080/10715760100300181
|View full text |Cite
|
Sign up to set email alerts
|

The role of nitric oxide in paraquat-induced cytotoxicity in the human A549 lung carcinoma cell line

Abstract: Paraquat (PQ) is a well-known pneumotoxicant that exerts its toxic effect by elevating intracellular levels of superoxide. In addition, production of pro-inflammatory cytokines has possibly been linked to PQ-induced inflammatory processes through reactive oxygen species (ROSs) and nitric oxide (NO). However, the role of NO in PQ-induced cell injury has been controversial. To explore this problem, we examined the effect of NO on A549 cells by exposing them to the exogenous NO donor NOC18 or to cytokines; tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…•− 2 , not NO, play a key role in the cellular damage caused by PQ [26]. However, in PQ models of lung injury, injury that was previously attributed to the generation of reactive oxygen species was found to be related to the induction of NO synthesis and was totally preventable by inhibition of NO synthesis [60,61].…”
Section: •−mentioning
confidence: 93%
See 1 more Smart Citation
“…•− 2 , not NO, play a key role in the cellular damage caused by PQ [26]. However, in PQ models of lung injury, injury that was previously attributed to the generation of reactive oxygen species was found to be related to the induction of NO synthesis and was totally preventable by inhibition of NO synthesis [60,61].…”
Section: •−mentioning
confidence: 93%
“…Human lung epithelial cells treated with PQ also express significant amounts of iNOS mRNA [23]. Similarly, human-derived cell lines such as A549 lung carcinoma [26] or the human neuroblastoma-derived cell line SH-SY5Y [27] show upregulation of iNOS expression after PQ exposure.…”
Section: Paraquat and Nitric Oxide Synthasesmentioning
confidence: 95%
“…Chang et al [3] demonstrated that the L-arginine-NO pathway contributes to LI induced by hyperoxia, and Tomita et al [21] also showed that an NO donor has deleterious effects in a lung carcinoma cell line. In contrast, the production of NO has been shown to be protective in tissue injury [1,5,19,27].…”
Section: Discussionmentioning
confidence: 99%
“…Because NO is a vasodilator, increased production may benefit the brain after injury [111]. On the other hand, excess production of NO can cause neurodegeneration manifesting as stroke, PD and HIV dementia [101,112]. NO can form adducts with mitochondrial enzymes and dysregulate mitochondrial function.…”
Section: Nitric Oxide Synthasementioning
confidence: 99%